The role of HIPEC in the treatment of peritoneal carcinomatosis from gastric cancer: between lights and shadows. Issue 2 (February 2015) - Di Vita, Maria; Cappellani, Alessandro; Piccolo, Gaetano; Zanghì, Antonio; Cavallaro, Andrea; Bertola, Giulio; Bolognese, Antonio; Facchini, Gaetano; D'Aniello, Carmine; Di Francia, Raffaele; Cardì, Francesco; Berretta, Massimiliano
Abstract : Gastric cancer is one of the most dreadful neoplastic diseases and remains the second cause of cancer death worldwide. Patients who develop peritoneal metastasis have a poor prognosis, with a median survival of less than 6 months. Despite being the cause of 60% of deaths from gastric cancer, peritoneal metastasis can still be considered a local disease and a local multidisciplinary approach can improve the prognosis even in this end-stage disease. At present, hyperthermic intraperitoneal chemotherapy (HIPEC) is the most widely accepted treatment for peritoneal surface diseases and can be performed in patients with different stages of cancer and with various antitumoral drugs. We performed a systematic review of the current status of HIPEC in the treatment of gastric peritoneal metastasis in an attempt to obtain answers to the questions that still remain: do results differ with these different methods? Does HIPEC exert a significant effect on the intracavitary delivery of drugs? Which patients should be treated and which should not? What can we expect from this approach in terms of survival, morbidity, and mortality? On reviewing the literature, despite the lack of trials comparing the different methods, we found that HIPEC has been shown to be an effective tool whenever a complete or an almost complete resection of the peritoneal implants can be performed. Therefore, it is advisable to refer all at-risk patients to specialized centers to be enrolled in randomized trials to achieve truly reliable results.